71 Prevalence and progression of the juvenile pattern in the electrocardiogram of adolescents. (June 2018) - Basu, Joyee; Malhotra, Aneil; Styliandis, Vasileios; Miles, Harshil DhutiaChris; Parry-Williams, Gemma; Tome, Maite; Sharma, Sanjay; Papadakis, Michael
Abstract : Background: The juvenile ECG pattern is defined as T wave inversion (TWI) in 2 contiguous anterior leads (V1 to V3) in individuals<16 years of age. This is due to electrical predominance of the right ventricle in infancy which gradually resolves with normalisation of the T waves post-puberty. Anterior TWI, however, is also the hallmark of arrhythmogenic cardiomyopathy. The recent international guidelines for electrocardiographic (ECG) interpretation in athletes do not recommend further evaluation of the juvenile ECG pattern in the absence of symptoms or significant family history of cardiac disease. Purpose: To assess the prevalence of the juvenile ECG pattern in a large, unselected population of adolescents and assess its evolution through puberty. Methods: Between 2011 and 2013, 7162 individuals between the ages of 13–16 years underwent voluntary cardiac screening with a health questionnaire and ECG. Individuals with the juvenile ECG pattern were invited for repeat ECG on an annual basis. ECGs from both the primary and final consultation were evaluated by two investigators for the presence of the juvenile pattern. Individuals with persistent TWI beyond V2 aged 16 years were referred for comprehensive evaluation. Results: A juvenile ECG pattern was observed in 430 (6%) individuals. The presence of a juvenile ECG pattern was more common in females (11% of females) than males (5% of males) (p<0.0001). The overall prevalence of the juvenile pattern reduced with increasing age (figure 1); this was the case for both TWI limited to leads V1-V2 and TWI extending beyond V2 (Figure 1). During a mean follow-up of 1.8±0.98 years, 162 subjects attended for a repeat ECG. 158 (98%) of these individuals demonstrated resolution of the juvenile pattern. The remaining 4 cases underwent further evaluation and follow-up. After a period of 5.1±0.3 years, none of these individuals demonstrated any phenotypic features of cardiomyopathy. Conclusion: The prevalence of the juvenile pattern in the general population between 13–16 years is 6%. It is more common in females and reduces significantly with age. The vast majority (98%) of juvenile ECGs resolve by the age of 16 years. Persistence of the juvenile ECG pattern over the 16 years is rare and should be evaluated further for cardiomyopathy.